Heavy oil hydrodesulfurization and carbon residue removal catalyst and preparation method thereof
By adding carbon alcohol and polystyrene to the macroporous sulphite, combining acidic metals and amino acid complexing agents, a heavy oil hydrodesulfurization and deresolvation catalyst with optimized pore structure was prepared, which solved the problem of fast catalyst deactivation, achieved efficient desulfurization and residual carbon conversion, and extended the service life of the catalyst.
Patent Information
- Application Number
- CN202311432016.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
The pore volume and pore size distribution of existing heavy oil hydrodesulfurization and deresolvation catalysts are not suitable for the diffusion and reaction of colloids and asphaltene in heavy oils, resulting in fast catalyst deactivation and short service life.
By adding carbon alcohol and polystyrene as pore expansion agent to the macroporous slurry, combined with acid metal impregnation liquid and amino acid complexing agent, a catalyst with optimized pore structure was prepared, increasing the pore content of 15-20nm and 20-30nm.
The desulfurization rate and residual carbon conversion capacity of the catalyst are improved, the service life of the catalyst is extended, and the operation cost is reduced.
Smart Images

Figure BDA0004523929660000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a heavy oil hydrodesulfurization and carbon residue removal catalyst and a preparation method thereof. Background Art
[0002] As crude oil becomes heavier and worse, the demand for light oil products increases, and the requirements for lightening heavy oil products are getting higher and higher. Heavy oil is the heaviest component in crude oil, usually accounting for 40-60% of crude oil, and its properties are significantly inferior to fractions such as gas oil with a lower boiling range. Residue oil has a complex composition, a large average molecular weight, high viscosity, high density, and contains a large amount of harmful elements and non-ideal components such as metals, sulfur, nitrogen, colloids, asphaltene, etc., which makes it very difficult to process.
[0003] Fixed bed residue oil hydrogenation technology is currently the most widely used heavy oil hydrogenation treatment technology. In the presence of catalyst and hydrogen, the process performs hydrodesulfurization, denitrogenation, carbon removal and metal removal on the residue oil. The hydrogenated residue oil will become a high-quality catalytic cracking feed, and then the heavy oil will be converted into light oil products. In the fixed bed residue oil hydrogenation industrial device, the desulfurization and carbon removal catalyst is loaded behind the demetallization catalyst. Most of the metal and sulfur impurities in the residue oil exist in colloids and asphaltene, which are the components with the largest molecular weight and the most complex structure in the petroleum components. They have large diffusion resistance and are prone to pore blockage (causing catalyst deactivation). They must have a large pore volume to facilitate the passage of impurity-containing macromolecules, react inside the catalyst pores, and increase the demetallization capacity; and maintain a large specific surface area, which is conducive to the desulfurization and carbon removal activity. In the fixed bed or boiling bed residue oil hydrogenation industrial device, after the inferior heavy oil passes through the demetallization catalyst bed, the asphaltene and colloid react and the size is reduced. Therefore, when preparing the residual oil hydrodesulfurization and carbon removal catalyst, the 15-20nm and 20-30nm pore contents are appropriately increased in a directional manner. While maintaining the desulfurization and carbon removal activity, the asphaltene and colloid after the reaction of the demetallization catalyst bed are easy to enter the pores for reaction, thereby slowing down the deactivation rate of the desulfurization and carbon removal catalyst, extending the service life of the catalyst, and increasing the operation cycle of the device.
[0004] CN106622314A discloses a high-activity hydrorefining catalyst and a preparation method thereof, wherein water is used as a solvent to prepare a slurry containing silicon-phosphorus-alumina, a boron-containing compound, a VIB group metal compound and a VIII group metal compound are added to the slurry, a filter cake and a filtrate are obtained by filtration, the filtrate is mixed with SB powder and a peptizing agent to obtain an adhesive, and the adhesive and the filter cake are successively rolled, formed, dried and calcined to obtain the hydrorefining catalyst. The catalyst has a small pore volume and a fast deactivation rate.
[0005] CN108102711B provides a combined process for producing needle coke, wherein the raw oil enters a catalytic cracking device, the catalytic oil slurry obtained after reaction separation is mixed with hydrogen and then enters an ebullated bed reactor, the liquid product heavy component obtained after separation of the reaction effluent of the ebullated bed reactor enters a coking device, the oil and gas generated by the coking reaction are separated to obtain gas, coking gasoline, coking diesel and coking wax oil, and the needle coke generated after the reaction cycle is completed is deposited in the coking device. In the method of the present invention, the catalytic section of the ebullated bed reactor is filled with a hydroprocessing catalyst, and the specific surface area of the special catalyst in the present invention is 120m 2 / g~300m 2 / g, preferably 160m 2 / g~280m 2 / g; pore volume is 0.2mL / g~0.8mL / g, preferably 0.4mL / g~0.6mL / g; average pore diameter is 8nm~13nm, preferably 9nm~11nm and the following pore size distribution: the volume of pores with diameters of 4nm~10nm accounts for 70%~80% of the total pore volume, and the volume of pores with diameters of 15nm accounts for 5%~10% of the total pore volume. The process of this invention is complicated, and the pore volume and diameter of the catalyst used are small, which is not conducive to the diffusion of macromolecules such as asphaltene, and the required hydrogenation process conditions are relatively harsh. Although sulfur impurities in the catalytic oil slurry can be removed, aromatics are lost.
[0006] CN1181409A discloses a residual oil hydrotreating catalyst and its preparation method, which uses γ-Al2O3 as a carrier to support metal elements of Group VIII and Group VIB, and is characterized in that the pore volume of the catalyst is 0.30-0.60 mL / g and the specific surface area is 120-200 m 2 / g, the average pore size is 9.0-13.0nm, and the pore volume with a pore size of 7.0-13.0nm accounts for more than 80% of the total pore volume. The catalyst prepared by this method has a larger specific surface area, a small macropore ratio, poor resistance to metal poisoning, and rapid deactivation.
[0007] CN1417300A discloses a hydrogenation catalyst and its preparation method. The preparation method of the catalyst comprises impregnating a macroporous alumina carrier with a solution containing metal compounds of Group VIB and Group VIII. The preparation method of the alumina carrier comprises extruding a mixture of pseudo-boehmite, acid, water and an extrusion aid into a molded product. The molded product is quickly dried within 35 minutes at 90-300°C and calcined at 600-800°C in a steam-containing atmosphere for at least 0.5 hours. The pore distribution of the obtained alumina carrier is such that pores with a diameter of 10-20nm account for 70-90% of the total pore volume.
[0008] CN1103009A discloses a method for preparing a heavy oil hydrodemetallization catalyst carrier, which is prepared by mixing two aluminum hydroxide precursors with different pore size distributions, adding carbon black and surfactant as pore-enlarging agents, and forming a double-pore alumina carrier through kneading, drying and calcining. This method has strict requirements on the precursor alumina raw material, requires the addition of more surfactants, and has a high cost. Summary of the invention
[0009] The object of the present invention is to provide a heavy oil hydrodesulfurization and carbon residue removal catalyst and a preparation method thereof. The method has a simple process and low cost. The prepared catalyst has a good pore structure, which is beneficial to the adsorption and removal of colloid and asphaltene macromolecules in the heavy oil. While promoting the conversion and desulfurization of carbon residue, it can also extend the service life of the catalyst.
[0010] To achieve the above-mentioned purpose, the present invention provides a method for preparing a heavy oil hydrodesulfurization and carbon removal catalyst, comprising the following steps: adding an extrusion aid and a pore expanding agent to macroporous pseudo-boehmite for mixing, then adding an acidic metal impregnation solution, kneading, molding, drying and roasting to obtain a catalyst; the pore expanding agent comprises carbon alcohol and polystyrene.
[0011] In the preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention, the carbon alcohol is octadecyl alcohol or tetracosyl alcohol.
[0012] The preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention comprises the following steps: the carbon alcohol is added in an amount of 0.5wt% to 6wt% of the alumina content in the pseudo-boehmite, preferably 2% to 4%; the polystyrene is added in an amount of 2wt% to 8wt% of the alumina content in the pseudo-boehmite, preferably 4wt% to 6wt%.
[0013] The preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention, the specific surface area of the macroporous pseudo-boehmite is ≥330m 2 / g, pore volume ≥1.15ml / g.
[0014] The preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention comprises an active metal precursor, an inorganic acid and a complexing agent in the acidic metal impregnation solution.
[0015] In the preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention, the complexing agent is an amino acid substance, and the added amount is 1wt% to 15wt% of the pseudo-boehmite, preferably 3wt% to 10wt%.
[0016] In the preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention, the complexing agent is one or more of arginine, histidine and lysine.
[0017] The preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention, the active metal in the acidic metal impregnation solution is a metal of Group VIB and / or Group VIII as a hydrogenation active metal component, preferably the active metal is at least one of Mo and W and at least one of Ni and Co. The precursor of the Mo element is one or more of ammonium molybdate, sodium phosphomolybdate, and ammonium phosphomolybdate; the precursor of the W element is ammonium tungstate, tungsten nitrate, and ammonium metatungstate; the precursor of the Ni element is one or more of nickel nitrate, nickel acetate, and basic nickel carbonate; the precursor of the Co element is one or more of cobalt nitrate, basic nickel cobalt carbonate, and cobalt naphthenate. In terms of oxides, molybdenum and / or tungsten account for 8wt% to 20wt% of the total mass of the catalyst, and nickel and / or cobalt account for 2wt% to 5wt% of the total mass of the catalyst.
[0018] In the preparation method of the heavy oil hydrodesulfurization and carbon removal catalyst described in the present invention, the inorganic acid is one or more of phosphoric acid, nitric acid and hydrochloric acid, and the amount of the inorganic acid is not particularly limited. The role of the inorganic acid is to dissolve the active metal precursor, and those skilled in the art can adjust it according to actual conditions.
[0019] In the preparation method of the heavy oil hydrodesulfurization and carbon removal catalyst described in the present invention, the extrusion aid is a cellulose material, and the added amount is 1wt% to 6wt% of the alumina content in pseudo-boehmite, preferably 2 to 4wt%. The cellulose material is a commonly used material in the field, and specifically can be methyl cellulose, ethyl cellulose, and hydroxymethyl cellulose, and the present invention does not make special limitations.
[0020] The preparation method of the heavy oil hydrodesulfurization and carbon removal catalyst of the present invention adopts a screw extruder in the molding process, and the extrusion pressure is 15-50Mpa. The shape of the catalyst can be changed according to needs, such as cylinder, clover, four-leaf clover and sphere; the drying temperature of the drying process is 100-200°C.
[0021] The preparation method of the heavy oil hydrodesulfurization and carbon residue removal catalyst of the present invention has the following characteristics: the calcination temperature is 500-900°C, preferably 680-850°C, and the calcination time is 0.5-6 hours.
[0022] To achieve the above purpose, the present invention also provides a catalyst prepared by the method, with a pore volume of 0.60-0.95 ml / g, pores of 15nm-20nm accounting for 40%-60% of the total pore volume, and pores of 20-30nm accounting for 25%-35% of the total pore volume.
[0023] Beneficial effects of the present invention:
[0024] The method provided by the present invention first uses macroporous pseudo-boehmite, adds carbon alcohol and polystyrene, the polystyrene physically expands the pores to 15-20nm, the hydroxyl groups in the carbon alcohol are combined with the hydroxyl groups in the macroporous pseudo-boehmite, and the isomerized carbon chains expand the pores to 20-30nm. The increase in the macropore ratio helps asphaltene and colloid macromolecules to react and transform inside the catalyst pores, thereby improving the desulfurization rate; the addition of an amino acid complexing agent improves the dispersion of metal salts and promotes the conversion of residual carbon.
[0025] The catalyst prepared by the method provided by the present invention has a higher desulfurization effect and residual carbon conversion capacity. DETAILED DESCRIPTION
[0026] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0027] Example 1
[0028] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 3.5g methyl cellulose (1wt%), 1.8g octadecyl alcohol (0.5wt%) and 7g polystyrene (2wt%), mix well; add 500ml Mo-Ni-P solution (catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 15g arginine and stir to dissolve completely, add water to make up to 500ml; then extrude into a four-leaf clover shape with a particle size of 1.4-1.6mm on a front extrusion single screw extruder, extrusion pressure 15MPa, dry at 100℃ for 3 hours, calcined at 700℃ for 6 hours, to obtain catalyst A1. Catalyst properties are shown in Table 1.
[0029] Example 2
[0030] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 3.5g methyl cellulose (1wt%), 20g octadecyl alcohol (6wt%) and 28g polystyrene (8wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 45g histidine and stir to dissolve completely, add water to make up to 500ml; then extrude into a clover shape with a particle size of 1.6mm on a front extrusion single screw extruder, extrusion pressure 40MPa, dry at 200℃ for 3 hours, and then calcine at 900℃ for 3 hours to obtain catalyst A2. Catalyst properties are shown in Table 1.
[0031] Example 3
[0032] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 20g methyl cellulose (6wt%), 20g octadecyl alcohol (6wt%) and 10g polystyrene (3wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 45g lysine and stir to dissolve completely, add water to make up to 500ml; then extrude into a cylindrical shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 25MPa, dry at 120℃ for 3 hours, and then roast at 500℃ for 6 hours to obtain catalyst A3. Catalyst properties are shown in Table 1.
[0033] Example 4
[0034] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 10g methyl cellulose (3wt%), 10g tetracosanol (3wt%) and 28g polystyrene (8wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO310wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add 50g serine, add water to make up to 500ml; then extrude into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, dry at 120℃ for 3 hours, and then roast at 850℃ for 5 hours to obtain catalyst A4. Catalyst properties are shown in Table 1.
[0035] Example 5
[0036] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 10g methyl cellulose (3wt%), 10g tetracosanol (3wt%) and 10g polystyrene (3wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add 75g arginine, add water to make up to 500ml; then extrude into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 15MPa, dry at 120℃ for 3 hours, and then calcine at 900℃ for 0.5 hours to obtain catalyst A5. Catalyst properties are shown in Table 1.
[0037] Example 6
[0038] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 10g methyl cellulose (3wt%), 20g tetracosanol (6wt%) and 10g polystyrene (3wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add 15g lysine, add water to make up to 500ml; then extrude into a cylindrical shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 25MPa, dry at 120℃ for 3 hours, and then calcine at 800℃ for 5 hours to obtain catalyst A6. Catalyst properties are shown in Table 1.
[0039] Comparative Example 1
[0040] According to the method described in Chinese patent CN106622314 A, 25g of molybdenum trioxide and 16g of basic nickel carbonate were added to the slurry containing silicon-phosphorus-alumina, filtered to obtain a filter cake and a filtrate, the filtrate was mixed with SB powder and a peptizing agent to obtain an adhesive, the adhesive and the filter cake were extruded into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, dried at 120°C for 3 hours, and then calcined at 800°C for 5 hours to obtain catalyst B1. The catalyst properties are shown in Table 1.
[0041] Comparative Example 2
[0042] According to the method described in Chinese patent CN1181409A, 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 80g ammonia solution (containing 3% ammonia), knead for 30min, add 240g acetic acid acidic aqueous solution, knead for 40min, extrude into strips, calcine at 800℃ to prepare a carrier, add 150ml Mo-Ni-P solution (containing MoO3 10wt%, NiO 5wt%) for impregnation, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 25g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 16g basic nickel carbonate and stir until completely dissolved, and add water to make up to 150ml; after spraying, filter out excess solution, dry at 120℃ for 3 hours, and then calcine at 500℃ for 4 hours to obtain catalyst B2.
[0043] Comparative Example 3
[0044] According to the method described in Chinese patent CN1417300A, 300 g of pseudo-boehmite (specific surface area 330 m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), mixed evenly with 3.9g nitric acid with a concentration of 65wt%, 3g sesbania powder and 120g deionized water, and extruded into a 1.6mm clover shape on an extruder. The mixture was dried by forced air at 110°C. After drying, 100% water vapor was introduced into the dried molded product at 750°C and calcined for 5 hours to obtain a carrier. 150ml of Mo-Ni-P solution (containing MoO3 10wt%, NiO 3.5wt%) was added to the obtained carrier for impregnation, wherein the Mo-Ni-H3PO4 solution was prepared as follows: 25g of molybdenum trioxide was added to 100ml of H3PO4 solution and stirred to dissolve completely, then 16g of basic nickel carbonate was added and stirred until completely dissolved, and water was added to make up to 150ml. After spray impregnation, the excess solution was filtered off, dried at 120°C for 3 hours, and then calcined at 500°C for 4 hours to obtain catalyst B3.
[0045] Comparative Example 4
[0046] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g, dry basis content 70wt%), add 3.5g methyl cellulose (1wt%), 2g n-propanol (0.5wt%) and 7g polystyrene (2wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 15g arginine and stir to dissolve completely, add water to make up to 500ml; then extrude into a four-leaf clover shape with a particle size of 1.4-1.6mm on a front extrusion single screw extruder, extrusion pressure 15MPa, dry at 100℃ for 3 hours, calcined at 700℃ for 6 hours, and obtain catalyst B4. Catalyst properties are shown in Table 1.
[0047] Table 1 Catalyst properties
[0048]
[0049] The results in Table 1 show that, compared with the comparative example, the specific surface area and pore volume of the catalyst prepared by the method described in the embodiment of the present invention are greater than those of the comparative example, and the content of pores with pore diameters of 15-20 nm and 20-30 nm is significantly higher than that of the comparative example.
[0050] The activity stability of the catalyst in Table 1 was evaluated. The evaluation conditions are shown in Table 2, and the evaluation results are shown in Table 3.
[0051] Table 2 Catalyst evaluation conditions
[0052] Heavy oil properties Density (20℃) / g·cm-3 1.078 Sulfur, wt% 3.6 Carbon residue, wt% 12.1 Process conditions Reaction temperature, °C 385 Hydrogen partial pressure, MPa 16 <![CDATA[Space velocity, h -1 > 0.4 Hydrogen / Oil Ratio 700
[0053] Table 3 Evaluation results
[0054] catalyst A1 A2 A3 A4 A5 A6 B1 B2 B3 B4 Sulfur content, wt% 0.49 0.44 0.48 0.46 0.47 0.45 0.50 0.49 0.51 0.53 Carbon residue, wt% 5.5 5.1 5.2 5.4 5.4 5.0 5.8 5.9 5.6 6.0
[0055] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a heavy oil hydrodesulfurization and carbon removal catalyst, characterized in that: The following steps are involved: An extrusion aid and a pore expanding agent are added to macroporous pseudo-boehmite for mixing, and then an acidic metal impregnation solution is added, kneaded, molded, dried and calcined to obtain a catalyst; the pore expanding agent includes carbon alcohol and polystyrene.
2. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 1, characterized in that: The carbon alcohol is octadecyl alcohol or tetracosyl alcohol.
3. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 1, characterized in that: The amount of carbon alcohol added is 0.5wt% to 6wt% of the aluminum oxide content in the pseudo-boehmite; the amount of polystyrene added is 2wt% to 8wt% of the aluminum oxide content in the pseudo-boehmite.
4. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 1, characterized in that: The specific surface area of the macroporous pseudo-boehmite is ≥330m 2 / g, pore volume ≥1.15ml / g.
5. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 1, characterized in that: The acidic metal impregnation solution comprises an active metal precursor, an inorganic acid and a complexing agent.
6. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 5, characterized in that: The complexing agent is an amino acid substance, and the added amount is 1wt% to 15wt% of the pseudo-boehmite.
7. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 6, characterized in that: The complexing agent is one or more of arginine, histidine and lysine.
8. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 5, characterized in that: The inorganic acid is one or more of phosphoric acid, nitric acid and hydrochloric acid.
9. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 5, characterized in that: The active metal is at least one of Mo and W and at least one of Ni and Co.
10. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 1, characterized in that: The extrusion aid is a cellulose substance, and the added amount is 1wt% to 6wt% of the alumina content in the pseudo-boehmite.
11. The method for preparing a heavy oil hydrodesulfurization and carbon residue removal catalyst according to claim 1, characterized in that: The calcination temperature is 500-900° C., and the calcination time is 0.5-6 hours.
12. The catalyst prepared by the method according to any one of claims 1 to 11, characterized in that: The pore volume is 0.60-0.95 ml / g, pores of 15 nm-20 nm account for 40%-60% of the total pore volume, and pores of 20-30 nm account for 25%-35% of the total pore volume.
Citation Information
Patent Citations
Hydrodemetalization catalyst for residual oil and preparation method for hydrodemetalization catalyst
CN105983417A
Catalyst for hydrogen desulfurization of catalytic cracking gasoline and preparation method of catalyst
CN107081155A
Residual oil hydrotreating catalyst and preparation method thereof
CN111001411A
Titanium-containing residual oil hydrotreating catalyst and preparation method thereof
CN111001412A
Hydrorefining catalyst for hydrocarbon and its preparing process
CN1289827A